Pengembangan Paket Kuliner Lokal Desa Ngadas Untuk Mendukung Wisata Taman Nasional Bromo Tengger Semeru (TNBTS) - Panji Deoranto; Susenohaji; Claudia Gadizza Perdani; Elok Waziiroh; Saundra Rosallina Lutfi (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
This service involves members consisting of lecturers, one of whom holds a minimum doctoral degree, while the other members hold a minimum master degree. While the other parties involved were students from the Community Service (KKN) and the Ngadas Village community as the main focus of the service. The service method uses a direct approach to the community by conducting training and mentoring gradually and continuously so that positive and significant results are obtained and beneficial to the community. Aside from the cultural aspect, the other wealth owned by Ngadas Village is the result of its agro-industry. Because of its location at an altitude of 2200 masl with an area of around 395 ha with hilly topography. Because it is more than 2000 meters above sea level, the temperature in Ngadas tends to be cold, the temperature around Ngadas ranges from 0 ° C to 20 ° C. This is what makes Ngadas Village very suitable for use as a farming location. There are a lot of plants that can be found in this village and are able to live well, including various kinds of vegetables, fennel, which are typical of the Ngadas village, and the best quality is potatoes. Potatoes in Ngadas Village are special because at first the seeds came from Australia and continued to grow until now.